Management of life-threatening aortoesophageal fistula: experiences learned from eight patients. (April 2021) - Chen, Chengshi; Kim, Jong Woo; Shin, Ji Hoon; Kwon, Yohan; Kim, Jinoo; Lee, In Joon
Background: Aortoesophageal fistula (AEF) is a rare but fatal condition causing massive upper gastrointestinal bleeding. Purpose: To report our experiences in the management of life-threatening AEF. Material and Methods: A total of eight patients (seven men, one woman; mean age = 59.4 years; age range = 43‒76 years) presenting with AEF between 2005 and 2018 were recruited from three different Korean hospitals. The medical records of these patients were reviewed for patient demographics, clinical features, diagnostic and therapeutic modalities, and outcomes. Results: Two patients died as a result of massive hemorrhage before endovascular or surgical treatment could be undertaken. Of the six patients who were treated, five underwent endovascular interventions: embolization of the fistula using n-butyl cyanoacrylate (NBCA) and subsequent thoracic endovascular aortic repair (TEVAR) in two patients; TEVAR alone in two patients; and NBCA embolization alone in one patient. Among them, three patients who received TEVAR with or without NBCA embolization in a timely fashion recovered and were discharged. One patient who received delayed TEVAR died of disseminated intravascular coagulation, and one who received NBCA embolization alone died of hemorrhagic shock, both dying within three days of treatment. The remaining patient who underwent surgical aortic repair is alive after 13 years. Conclusion: Rapid identification and surgical treatment are necessary to increase the likelihood of survival, if emergency surgery is feasible. TEVAR in a timely fashion facilitates hemodynamic stabilization by rapidly controlling hemorrhage and saves the patient's life.